Fragmentation and Coordination of REDD+ Finance under the Paris Agreement Regime - Dong-hwan Kim (MDPI AG, 2021)
Under the Kyoto Protocol regime, various forms of financial support have been committed to helping the implementation of reducing emissions from deforestation and forest degradation, as well as fostering conservation, the sustainable management of forests, and the enhancement of forest carbon stocks (REDD+) in developing countries. We analyzed the fragmentation of REDD+ finance and suggested methods for its coordination under the Paris Agreement regime. The fragmentation of REDD+ finance was observed, but it was lower than that of general official development assistance (ODA). However, we found that the trend of fragmentation in REDD+ financing is different from that of general ODA, with a few major donors occupying a large portion of the total size of committed REDD+ finance. Thus, it may not be appropriate to consider the fragmentation of REDD+ finance merely as an obstacle that needs to be decreased. Still, the total amount of REDD+ finance should be increased and adjusted for various donor–recipient relationships, in consideration of the REDD+ finance options in the Paris Agreement. Some REDD+ countries have made progress in national REDD+ and accomplished emission reductions. However, REDD+ finance needs to be stratified considering the progress of national REDD+. For such forms of cooperation, an information-sharing and monitoring system that collects information on ongoing REDD+ cooperation, the commitment and expenditure of REDD+ finance, and the support needs of REDD+ countries at a global level should be established. Multilateral organizations need to provide safeguarding functions for developing countries that are isolated from bilateral REDD+ finance.